The role and mechanism of TSC in kidney diseases: a literature review - Qiulin Luo; Xinguo Zheng; Ye Xu; Yuxi Fan; Hedong Zhang; Tengfang Li; Xiangqi Zhang; Longkai Peng; Xin Jiang; Helong Dai (BMC Nephrology)
Abstract Background Tuberous sclerosis complex (TSC) is an autosomal dominant genetic disorder characterized by multisystem involvement, primarily caused by loss-of-function mutations in the TSC1 or TSC2 genes. TSC is a key integrator of metabolic signaling and cellular stress and has become an important regulator in several kidney diseases. Summary TSC1 and TSC2 can be used not only as genetic markers for disease diagnosis, but also as potential immunotherapeutic targets for kidney disease. Recent studies on the pathogenesis of TSC may provide guidance for developing new treatment strategies for kidney diseases. Key messages Therefore, we systematically reviewed the molecular biology of TSC and their signaling pathway, regulation of cell metabolism, and immune response in acute renal injury, chronic kidney disease, diabetic kidney disease, renal cysts, benign and malignant intrarenal tumors, and renal angiomyolipomas. We also summarize the efficacy and adverse effects of mTOR inhibitors in the treatment of TSC-related kidney diseases.